The Effectiveness of The Correctional Development Program in Changing the Behaviour of Prisoners: Study at the Langkat Class III Youth Correctional Institution - Orisalsalina Br Surbakti; Syaiful Azmi Hasibuan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The social issue in giving to prisoners who have committed criminal acts of narcotics abuse is the prisoner's right to receive a reduced sentence if they have good behavior while undergoing training. In principle, remission is to create a correctional system that leads to the process of rehabilitation and resocialization of prisoners. The correctional system which started from prison then turned into a correctional system. Penitentiary institutions are no longer a place for revenge, but are a place for convict development.The nature of the research used is normative legal research and the data collection method used in this research is secondary data obtained through library research, namely by conducting research on various literature such as books, laws, with the aim of to look for concepts, or understandings related to the problem of Prison Criminal Efficiency in Changing Prisoner Behavior (Study at Class III Langkat Youth Correctional Institution. A convict is a person who is serving a sentence for a criminal offense or a convict who is serving his sentence in a correctional institution where some of his freedom has been lost. Whereas the regulations regarding remissions start from Government Regulation No. 32 of 1999, the conditions for granting remissions, one of which is for narcotics convicts, are the conditions for granting remissions so that their implementation reflects the values ​​of justice.The mechanism for the process of granting remissions for narcotics crimes in Narcotics Correctional Institutions is that the stages of granting remissions are carried out by submitting an application for remission to the Minister of Law and Human Rights. Then the Head of Prisons makes an assessment with the correctional assessment team of the prisoner. The Head of Prisons and the Correctional Observer Team then held a hearing to discuss the request for remission accompanied by supporting data.